The Bachelor’s Degree in Piano at FAMES and Its Relationship with the Labor Market in Espírito Santo: Challenges and Perspectives (Orfeu, 2025)
This research aimed to understand how pianists who graduated from the bachelor’s degree in Piano at FAMES establish connections between their musical training and professional practice in the State of Espírito Santo. The study was motivated by the current decline in demand for the referred course. To achieve the proposed objectives, data was collected and analyzed from institutional documents, and from semi-structured interviews conducted with program graduates to explore their experiences during their education and in the job market. The analysis of the results shows that, although the curriculum of the Bachelor’s degree in Classical Piano at FAMES has improved, it still does not fully meet the contemporary demands that musicians face in the job market, particularly within the context of Espírito Santo.
Keywords: Job market in music; FAMES; classical piano; Espírito Santo (State)